Whole genome sequencing of a rare rotavirus from archived stool sample demonstrates independent zoonotic origin of human G8P[14] strains in Hungary - Marton, Szilvia; Dóró, Renáta; Fehér, Enikő; Forró, Barbara; Ihász, Katalin; Varga-Kugler, Renáta; Farkas, Szilvia L.; Bányai, Krisztián (Virus research, 2017)
•The genome sequence and phylogenetic analysis of a human G8P[14] rotavirus strain is described.•The strain originates very likely from an animal host species.•Different P[14] strains detected in Hungary likely represent independent zoonotic events. Genotype P[14] rotaviruses in humans are thought to be zoonotic strains originating from bovine or ovine host species. Over the past 30 years only few genotype P[14] strains were identified in Hungary totaling<0.1% of all human rotaviruses whose genotype had been determined. In this study we report the genome sequence and phylogenetic analysis of a human genotype G8P[14] strain, RVA/Human-wt/HUN/182-02/2001/G8P[14]. The whole genome constellation (G8-P[14]-I2-R2-C2-M2-A11-N2-T6-E2-H3) of this strain was shared with another Hungarian zoonotic G8P[14] strain, RVA/Human-wt/HUN/BP1062/2004/G8P[14], although phylogenetic analyses revealed the two rotaviruses likely had different progenitors. Overall, our findings indicate that human G8P[14] rotavirus detected in Hungary in the past originated from independent zoonotic events. Further studies are needed to assess the public health risk associated with infections by various animal rotavirus strains.